Mental health - Ruggiero, Adriane (Detroit : Greenhaven Press, 2008)
Presents an overview of mental health care in the United States, discussing topics such as the history of mental health from the colonial era to the present, and current initiatives to improve care for the mentally ill.
Includes bibliographical references (p. 225-228) and index
Keywords: Mental health